Wood‐Inspired High‐Performance Ultrathick Bulk Battery Electrodes - Lu, Lei‐Lei; Lu, Yu‐Yang; Xiao, Zi‐Jian; Zhang, Tian‐Wen; Zhou, Fei; Ma, Tao; Ni, Yong; Yao, Hong‐Bin; Yu, Shu‐Hong; Cui, Yi (Advanced materials (Weinheim), 2018)
Ultrathick electrode design is a promising strategy to enhance the specific energy of Li‐ion batteries (LIBs) without changing the underlying materials chemistry. However, the low Li‐ion conductivity caused by ultralong Li‐ion transport pathway in traditional random microstructured electrode heavily deteriorates the rate performance of ultrathick electrodes. Herein, inspired by the vertical microchannels in natural wood as the highway for water transport, the microstructures of wood are successfully duplicated into ultrathick bulk LiCoO2 (LCO) cathode via a sol–gel process to achieve the high areal capacity and excellent rate capability. The X‐ray‐based microtomography demonstrates that the uniform microchannels are built up throughout the whole wood‐templated LCO cathode bringing in 1.5 times lower of tortuosity and ≈2 times higher of Li‐ion conductivity compared to that of random structured LCO cathode. The fabricated wood‐inspired LCO cathode delivers high areal capacity up to 22.7 mAh cm−2 (five times of the existing electrode) and achieves the dynamic stress test at such high areal capacity for the first time. The reported wood‐inspired design will open a new avenue to adopt natural hierarchical structures to improve the performance of LIBs. Inspired by the vertical microchannels in natural wood as the highway for water transport, an ultra‐thick bulk LiCoO2 (LCO) cathode with vertical channels is fabricated to enhance the transport of Li+. Remarkably, the fabricated LCO cathode shows low tortuosity and high Li‐ion conductivity, and can deliver high areal capacity up to 22.7 mAh cm−2.